Epidemiological and clinicopathological parameters related to the neoadjuvant chemotherapy for breast cancer during the COVID-19 crisis - Gontijo, Maria Fernanda da Motta Sperotto Valadares; Linhares, Letícia Martins de Araújo Campos; Campos, Luisa Lazarino de Souza; Sá, Marcela de Oliveira; Avelar, Caroline Cançado; Apolinário, João Pedro Costa; Diniz, Paulo Henrique Costa; de Avelar, José Tadeu Campos (Mastology, 2025)
Breast cancer, the second-leading cause of cancer-related deaths among women worldwide, is a complex and heterogeneous disease. Its socioeconomic aspects are recognized as determinants of clinical outcomes. The COVID-19 crisis negatively affected millions, particularly in impoverished macroregions like Brazil. Thus, influences on breast cancer patients’ journey may occur, particularly in the neoadjuvant settings, in which a coordinated and multidisciplinary approach is mandatory. The present study aimed to analyze the epidemiological and clinicopathological profile of breast cancer patients who underwent neoadjuvant chemotherapy during the pandemic in Brazil. Methods: This is a unicentric, retrospective, and descriptive cross-sectional study conducted by analyzing data obtained from electronic medical records of breast cancer patients who underwent neoadjuvant chemotherapy. Results: From March 2020 to December 2022, 55 patients underwent neoadjuvant chemotherapy. They presented an average age of 50.0 years (range 43.9–47.6). About 83.6% of the tumors were invasive ductal carcinomas, and the most prevalent molecular subtype was hormone receptor-positive. T2 tumors accounted for 50.9%, while compromised N1 axillary lymph nodes represented 52.7%. The most commonly used neoadjuvant chemotherapy combined anthracyclines, cyclophosphamide, and sequential taxane. Regarding postoperative pathological response, 42.2% showed a partial response after neoadjuvant treatment, and a complete pathological response of as high as 40.0% occurred. The luminal and hybrid luminal subtypes were those that achieved the greatest response to neoadjuvant therapy. The lack of pathological response was only found in the luminal molecular subtype. Conclusions: This study demonstrated the impacts of the COVID-19 pandemic on breast cancer patients’ journey. During this period of disruption in healthcare assistance, the disease presented at more advanced stages, but the pathologic complete response was higher than expected, and influences on chemotherapy decisions were not relevant. Overall, there were efforts to keep patients in the best breast cancer care.